Poaceae from Yanachaga-Chemillén National Park (Oxapampa, Peru). Part II: Pooideae, Centothecoideae, Arundinoideae, Chloridoideae and Panicoideae - La-Torre, María I. (2004)
This is a second part of biodiversity study of Poaceae family from Yanachaga-Chemillen National Park and surroundings places (Oxapampa, Pasco, Peru). This part is dedicated to diversity of follow subfamilies: Pooideae, Centohecoideae, Arundinoideae, Chloridoideae and Panicoideae. A total of 12 tribes, 37 genera and 63 species have been registered. Descriptions of genera and keys for genera and species are developed. Ecology, distribution and studied material are indicated.